Reproductive Justice, Public Black Feminism in Practice: A Reflection on Community-Based Participatory Research in Cincinnati - Carolette Norwood; Farrah Jacquez; Thembi Carr; Stef Murawsky; Key Beck; Amy Tuttle (Societies, 2022)
Research on reproductive justice has mainly, but not exclusively, appeared in academic literature in the context of grassroots social justice movements and as a theoretical framework for understanding the limitations of “reproductive choice” in the absence of social justice. But how can scholars design research to explore and understand reproductive (in)justice in the real lives of women of color? How can research partnerships between university scholars and community stewards be formed and sustained? What tensions and challenges are inherent in these efforts? And how can we find more equitable ways of sharing research findings and creating change with and not on behalf of our community? This paper reflects on the use of Community-Based Participatory Research (CBPR) in a reproductive justice research project focused on Black women residing in Cincinnati.